2019
DOI: 10.3390/ijms21010265
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone from the Salvia miltiorrhiza Bunge Attenuates Ethanol-Induced Liver Injury by Activation of AMPK/SIRT1 and Nrf2 Signaling Pathways

Abstract: Cryptotanshinone (CT), a diterpene that is isolated from Salvia miltiorrhiza Bunge, exhibits anti-cancer, anti-oxidative, anti-fibrosis, and anti-inflammatory properties. Here, we examined whether CT administration possess a hepatoprotective effect on chronic ethanol-induced liver injury. We established a chronic alcohol feeding mouse model while using C57BL/6 mice, and examined the liver sections with hematoxylin-eosin (H&E) and Oil Red O (ORO) staining. Further, we analyzed the lipogenesis, fatty acid ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…SIRT1 is downregulated during HSCs activation as demonstrated in in vitro studies, including TGFβ-stimulated LX2 cells [ 90 , 91 ], and activated rat [ 92 ] and mouse [ 90 , 93 ] primary HSCs. It has also been found downregulated in fibrotic liver tissues from in vivo studies in models such as CCl 4 [ 90 , 93 , 94 ], thioacetamide (TAA) [ 93 ] and ethanol-induced liver injury in mice [ 95 ], and CCl 4 [ 92 ] and BDL rat models [ 96 , 97 ], as well as in non-alcoholic fatty liver disease (NAFLD) patients liver tissues [ 98 ]. SIRT1 downregulation in hepatic fibrogenesis seems to be modulated in part by epigenetic mechanisms, including HDAC4 and lncRNA MALAT1-mediated SIRT1 repression [ 90 , 93 ].…”
Section: Acetylation/deacetylation Of Histones In Liver Fibrosismentioning
confidence: 99%
“…SIRT1 is downregulated during HSCs activation as demonstrated in in vitro studies, including TGFβ-stimulated LX2 cells [ 90 , 91 ], and activated rat [ 92 ] and mouse [ 90 , 93 ] primary HSCs. It has also been found downregulated in fibrotic liver tissues from in vivo studies in models such as CCl 4 [ 90 , 93 , 94 ], thioacetamide (TAA) [ 93 ] and ethanol-induced liver injury in mice [ 95 ], and CCl 4 [ 92 ] and BDL rat models [ 96 , 97 ], as well as in non-alcoholic fatty liver disease (NAFLD) patients liver tissues [ 98 ]. SIRT1 downregulation in hepatic fibrogenesis seems to be modulated in part by epigenetic mechanisms, including HDAC4 and lncRNA MALAT1-mediated SIRT1 repression [ 90 , 93 ].…”
Section: Acetylation/deacetylation Of Histones In Liver Fibrosismentioning
confidence: 99%
“…By Nrf2 induction, CT inhibits ROS production and subsequent oxidative stress to attenuate cell death. Also, CT induces AMPK/sirtuin 1 (SIRT1) axis to alleviate lipogenesis in liver (Nagappan, Kim, Jung, & Jung, 2020).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Cryptotanshinone, an active component from the herb Salvia miltiorrhiza , has been shown to possess pharmacological activities, such as anti‐inflammatory, anti‐oxidative, anti‐apoptosis and neuroprotection activities. [ 42‐44 ] Cryptotanshinone can increase ADAM10 level and promote non‐amyloidogenic α‐secretase processing of APP in SweAPP cortical neurons, which has been shown that improve learning and memory on AD rat model. [ 45 ] Cryptotanshinone could ameliorate the impaired learning and memory function of AD mice via shorten the latency of searching the hidden platform in directional swimming test, increase the time spent in swimming in the target quadrant in probe test, improve the activities of glutathione peroxidase (GSH‐Px) and SOD, and decrease the MDA content.…”
Section: Quinones and Its Role In Admentioning
confidence: 99%